Keanekaragaman Lumut di Kebun Botani Bangka Flora Society, Bangka. - Rosyanti Rosyanti; Budi Afriyansyah; Ida Haerida (PTTI, 2018)
Rosyanti, Budi Afriyansyah & Ida Haerida. 2018. Diversity of Bryophytes from Botanical Garden of Bangka Flora Society, Bangka. Floribunda 5(8): 315–321. — Botanical Garden of Bangka Flora Society is a place to conserve the diversity of flora of Bangka Belitung, and it is located in the village of Petaling Banjar, West Mendo District, Bangka Regency. Data collection using exploration methods. Bryophytes are found during the exploration are collected and identified. A total of 45 species of Bryophytes were recorded from the garden. Those consist of 30 species of mosses in 9 families and 15 species of liverwort in 4 families and 11 of them are new records for Sumatra. Five new recorded species of mosses for Sumatra are Anthrocormus schimperi Dozy & Molk., Calymperes polisotii Schwaegr., Syrrhopodon rufescens Hook. & Grev., Microdus macromorphus Fleisch., and Fissidens robinsonii Broth. Whereas Calypogeia arguta Nees & Mont. ex Nees, Frullania gracillis (Reinw. et al.) Dum., Frullania meyeniana Lindenb., Leptolejeunea elliptica (Lehm & Lindenb.) Schiffn., Schiffneriolejeunea pulopenangensis (Gottsche) Gradst., and Pallavicinia lyellii (Hook.) Carruth. are new recorded species of liverworts for Sumatra.Keywords: Bryophytes, botanical garden of Bangka Flora Society, new record. Rosyanti, Budi Afriyansyah & Ida Haerida. 2018. Keanekaragaman Lumut di Kebun Botani Bangka Flora Society, Bangka. Floribunda 5(8): 315–321. — Kebun Botani merupakan suatu kawasan konservasi keanekaragaman flora Bangka Belitung. Kebun Botani tersebut terletak di dusun Kampung Sawah desa Petaling Banjar, Kabupaten Bangka. Pengumpulan data menggunakan metode eksplorasi dan koleksi flora dengan cara jelajah. Lumut yang ditemukan selama penjelajahan di koleksi, kemudian dibuat herbarium dan diidentifikasi. Hasil penelitian menunjukkan terdapat 45 jenis lumut yang terdiri atas 30 jenis lumut sejati (9 suku) dan 15 jenis lumut hati (4 suku). Sebelas jenis lumut yang ditemukan di Kebun Botani merupakan rekaman baru untuk Sumatra. Lima jenis rekaman baru lumut sejati adalah Anthrocormus schimperi Dozy & Molk., Calymperes polisotii Schwaegr., Syrrhopodon rufescens Hook. & Grev., Microdus macromorphus Fleisch., dan Fissidens robinsonii Broth. Sedangkan 6 jenis lumut hati yang merupakan rekaman baru untuk Sumatra yaitu Calypogeia arguta Nees & Mont. ex Nees, Frullania gracillis (Reinw. et al.) Dum., Frullania meyeniana Lindenb., Leptolejeunea elliptica (Lehm & Lindenb.) Schiffn., Shiffneriolejeunea pulopenangensis (Gottsche) Gradst., dan Pallavicinia lyellii (Hook.) Carruth.Kata kunci: Lumut, kebun Botani Bangka Flora Society, rekaman baru.